Pendidikan Mitigasi Bencana Melalui Kampung Literasi pada Masyarakat Pesisir di Kabupaten Jember - Ningsih, Dian Rahayu; Indrianti, Deditiani Tri; Fajarwati, Linda (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2023)
Disaster mitigation education is education related to a series of efforts to minimize the impact of a disaster. In this case, disaster mitigation education is carried out in the Payangan Coast of Jember. The purpose of this research is to identify the knowledge, attitudes, and skills of the community related to disaster mitigation. Determination of the place in this study using the purposive area method in Sumberejo Village, Ambulu District, Jember Regency, precisely on the Payangan Coast. The technique for determining research informants uses snowball sampling where the sampling technique based on data sources is getting bigger and bigger and data is obtained through a rolling process from one respondent to another. Then for data collection techniques through interviews, observation, and documentation. Test the validity of the data using extended observations, increased persistence, and triangulation. In triangulation the researcher uses all three, namely triangulation of sources, techniques and time so that the data obtained is in accordance with what the researchers expect. In this study, data analysis techniques used data reduction, data display, and data verification. So the results of this study concluded that disaster mitigation education in coastal communities is obtained through the knowledge, attitudes, and skills that exist in coastal communities. In a disaster mitigation, it cannot be separated from a forum that is used to develop knowledge, attitudes, and skills that exist in the community, therefore it is necessary to have a literacy village that is used as a forum for disaster mitigation education. Keywords: Disaster Mitigation Education, Literacy Village